Pengaruh Suhu dan Kelembaban terhadap Produktivitas Jamur Tiram - Eteruddin, Hamzah; Padil; Dini, Isna Rahma; Huda, Feblil; Febrizal (JURNAL TEKNIK, 2024)
Indonesia is one of the countries that has various types of mushrooms, both those that are edible and those that are not. One type of edible mushroom is the oyster mushroom. In its growth, oyster mushrooms are greatly influenced by the temperature and humidity in the mushroom house. The purpose of this research is to determine the effect of temperature and humidity on mushroom productivity and to identify the optimal temperature and humidity for mushroom growth. The research method involved measuring temperature and humidity in the morning, afternoon, evening, and night every day for 2 months, namely June and July 2024. The temperature and humidity data collected were the daily averages. After obtaining the average daily temperature and humidity data, the next step was to observe the shape and color of the oyster mushrooms and collect data on the number of mushrooms obtained each day for 2 months. From the data analysis, it was found that the oyster mushrooms hardened and turned yellow when the temperature and humidity were unstable for mushroom growth. The optimal average temperature and humidity were 27°C and 82%, with the number of mushrooms obtained being 55kg/day.